2016
DOI: 10.3141/2558-07
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Longitudinal Arterial Performance and Traffic Signal Retiming Outcomes

Abstract: Agencies often find it difficult to justify investments in active traffic management. Historically, it has been a challenge to obtain data that would help make the case for those investments. While new data sources have emerged recently, there remains very little documentation of the potential long term benefits from signal retiming using associated performance measures. This study presents a use case for an active traffic management strategy on a signalized corridor over a 5-year period, during which traffic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…The first case study is located in Palm Beach, Florida as reported by Cambridge Systematics (2014). The second case study, located in Hamilton County, Indiana was reported in Lavrenz et al (2016). Both Cambridge Systematics (2014) and Lavrenz et al (2016) are the main sources of the inputs for these applications in TOPS-EIA.…”
Section: Overviewmentioning
confidence: 99%
See 4 more Smart Citations
“…The first case study is located in Palm Beach, Florida as reported by Cambridge Systematics (2014). The second case study, located in Hamilton County, Indiana was reported in Lavrenz et al (2016). Both Cambridge Systematics (2014) and Lavrenz et al (2016) are the main sources of the inputs for these applications in TOPS-EIA.…”
Section: Overviewmentioning
confidence: 99%
“…One of the primary objectives of the signal optimization project was to maximize the arrivals on green. Weekday traffic data was collected during three weeks in June before the optimization and one week in July after the optimization, 6 a.m. to 9 p.m. in 2010, as reported in Lavrenz et al (2016). The traffic signals studied in this analysis are operated under traffic actuated control.…”
Section: Project Descriptionmentioning
confidence: 99%
See 3 more Smart Citations